2020
DOI: 10.1093/geront/gnaa162
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Pure Panic”: The Portrayal of Residential Care in American Newspapers During COVID-19

Abstract: Background and Objectives This study examines the discursive construction of residential care during the COVID-19 pandemic in three leading American newspapers: The New York Times, USA Today, and The New York Post. Research Design and Methods A total of 54 news articles between 21 January and 8 May 2020 were identified from the LexisNexis academic database for analysis. The articles were analyzed using both a critical discour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 40 publications
1
33
0
1
Order By: Relevance
“…Hence, not only did many of the settings isolate their residents, but many of the settings also did not openly share information about the pandemic and its impact on residents, resulting in high levels of frustration and distrust among family members. This sense of concealment and limited transparency with regard to LTC settings is not unique to Israel as a recent study conducted in the United States has reported a similar sentiment (Allen & Ayalon, 2020). Their active involvement through banding together to protest against the restrictions and the rupture from the residents speaks to the importance of maintaining an open dialogue between the staff and the family members, and of working in collaboration with them to ensure that the priorities and personal values of the residents, who could not speak up for themselves during the lockdown, are heard and taken into account.…”
Section: Discussionmentioning
confidence: 92%
“…Hence, not only did many of the settings isolate their residents, but many of the settings also did not openly share information about the pandemic and its impact on residents, resulting in high levels of frustration and distrust among family members. This sense of concealment and limited transparency with regard to LTC settings is not unique to Israel as a recent study conducted in the United States has reported a similar sentiment (Allen & Ayalon, 2020). Their active involvement through banding together to protest against the restrictions and the rupture from the residents speaks to the importance of maintaining an open dialogue between the staff and the family members, and of working in collaboration with them to ensure that the priorities and personal values of the residents, who could not speak up for themselves during the lockdown, are heard and taken into account.…”
Section: Discussionmentioning
confidence: 92%
“…First of all, to avoid extensive distrust and collateral damage in the future, policy makers should openly address the identified issues related to isolation (cf. ( Allen and Ayalon, 2021 )), and collaborate with researchers in developing safe solutions that enable social contact among nursing home residents. Those responsible for designing new interactional protocols in nursing homes should acknowledge the contribution of FMs to the residents' well-being should be acknowledged in changing circumstances (cf.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are indications that this evidence is competing with a contrasting, negative narrative that seeks to lay the blame on the staff of care homes for the tragedies that COVID-19 wreaked upon so many residents. 37,38…”
Section: Discussionmentioning
confidence: 99%